Verbal Selective Reminding Test (six-trial administration): regression-based norms for a portuguese version - Neves, M.; Sousa, C.; Passos, A. M.; Ferreira, A. I.; Sá, M. J. (Applied Neuropsychology Adult, 2018)
The Verbal Selective Reminding Test (VSRT) is a widely used measure to evaluate verbal learning and memory associated with different neurological conditions. The goal of this study was to extend the use of the six-version trial of this test to the Portuguese population, through the production of adjusted normative data. The normative sample consists of 309 healthy participants aged between 20 and 70, with an educational level ranging from 4 to 23 years of formal. Gender, education, and age effects were explored. In addition, the reliability of the test was also analyzed and normative data produced. Gender, age, and education were significantly associated with VSRT performance. The test revealed excellent inter-rater reliability and good test–retest reliability. The normative data is presented as a regression-based formula to adjust test scores for gender, education and age. The correspondence between adjusted scores and percentile distribution was calculated. Since a test with appropriate norms is fundamental to an appropriate assessment of memory functioning, the normative data produced in this study improves the applicability of VRST for both clinical and research proposes in the Portuguese population. Further studies might also explore the adequacy of these norms for other Portuguese-speaking countries.